TEKNIK PEMERIKSAAN RADIOGRAFI OS HUMERUS PADA KASUS FRAKTUR 1/3 PROXIMAL OS HUMERUS DI INSTALASI RADIOLOGI RUMAH SAKIT UNIVERSITAS SUMATERA UTARA - TJUANDA, YUSRIWAN (JURNAL ILMIAH KOHESI, 2022)
Background: The humerus is the longest bone of the upper limb, showing a shaft and two ends (Pearce, 2009). We can generally understand that this bone is located between the shoulder and elbow. A fracture is a break in the continuity of the bone and this condition can be caused by direct or indirect trauma, underlying disease or repeated pressure on the bone. A fracture is a break in the continuity of the bone and this condition can be caused by direct or indirect trauma, underlying disease or repeated pressure on the bone. Research Method: the type of research used is qualitative with a case study approach. The data collection methods used in this research were observation, documents and in-depth interviews. Data analysis was carried out through the data reduction stage, presenting data in the form of open coding, drawing and drawing conclusions. Research Results: Humerus Os radiographic examination technique in fracture cases at the Radiology Installation of North Sumatra University Hospital. On the X-Ray examination of the Humerus Os with a fracture case in the patient with the name Mr. X, visible fracture in the proximal 1/3 of the right humerus with postetolateral dislocation and contraction. Joint gap. Description: fracture of the proximal 1/3 of the right humerus with postelolateral dislocation and contraction. Conclusion: The technique for radiographic examination of the humerus in cases of the proximal 1/3 of the humerus in the Radiology Installation of the North Sumatra University Hospital is to use basic projections, namely Antero-Posterior (AP) and Lateral.